Evaluation of reactions of commercial and autochthonous apple cultivars to common diseases in Serbia under natural infection - Balaž, Jelica; Ognjanov, Vladislav; Keserović, Zoran; Šućur, Aleksandra; Janse, Jaap; Popovic, Tatjana (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2017)
This study presents the results of a multiple-year evaluation (1991-1996; 2005-2007) of susceptibility of more than 100 apple cultivars to Venturia inaequalis, Podosphaera leucotricha and Erwinia amylovora under agroecological conditions existing in Serbia. Some of the most popular cultivars were found highly susceptible to V. inaequalis (Cripps Pink, Mutsu, Gloster 69, Wellspur); while Golden Delicious, Richared, Gala, Čačanska pozna, Čadel and Jonagold were susceptible; Idared, Granny Smith and Jonathan moderately susceptible; Lord Lamburne and London Pepping, as well as several autochthonous cultivars were moderately resistant; and a group of resistant cultivars included Prima, Priscilla, Williams Pride, Dayton, Enterprise, Gold Rush, Golden Orange, many of the Re-cultivars (Germany), as well as Baujade, Selena, Dukát, Produkta, Topaz, some older cvs. (Worcester Pearmain, Merton Worcester, James Grieve, Akane, Astilish, Astrachan Red and Discovery), some Co-op selections (USA) and NS hybrids (Serbia). Regarding powdery mildew, Idared and Jonathan were highly susceptible; Gala, Akane, Jonagold, Priscilla, Mutsu, Čačanska pozna, Golden Delicious, Granny Smith, Čadel and GoldRush were susceptible; Wellspur, Astrachan Red, Richared, Jonadel, Dayton and several autochthonous cultivars were moderately susceptible; Lord Lamburne, Astlisch, Prima, Champagne Reinette, Discovery and many autochthonous cultivars were moderately resistant; while most Re-cvs. (Germany), several cultivars from the Czech Republic, some selections from the USA and UK and most NS hybrids (Serbia) were resistant. Also, some cultivars showed variable susceptibility depending on location (Williams Pride, Gloster 69, Baujade and Produkta). E. amylovora was observed only in 2007 and at relatively low intensity (up to 12% infection). The highest disease severity was observed on cv. Elstar, then Granny Smith, Idared and Jonagored; while the lowest was found on Red Chief and Hapke apple trees.